The function of the urban informal sector in employment : evidence from Colombia 1984-2000 (2002)
The aim of this paper is to analyze the function of the informal sector in employment, its relationship to urban employment, with illustrative evidence from Colombia. The analysis is done for the period 1984 - 2000, which includes phases of boom and economic crisis as well as the implementation of neo-liberal reforms to national development. The paper summarizes four competing approaches to the conceptualization of the informal sector, and describes their measurement strategies. It argues that elements of state regulation are fundamental whereas firm size should not be considered as a defining element. Subsequently, it analyzes how the internal composition of the informal sector evolved, considering elements of state regulation, firm size, and dynamism of the economic activities. It examines the function of the informal sub-sectors in the urban labor market, using indicators such as relative earnings and size, and a crude indicator of labor mobility. At least three sub-sectors conforming the informal sector are identified: salaried workers of large and small firms, entrepreneurs and subsistence workers. It is argued that each sub-sector of the informal sector responds in different ways to prevailing economic conditions. The subsistence sub-sector supports the dualistic view, whereas the other two are integrated to the formal sector. No dominant sub-sector permits road-range generalizations about "the" informal sector.